PENGARUH JENIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG DAUN (Allium fistulosum L.) - Josina Irene Brigetha Hutubessy (Agriculture Faculty of Flores University, 2013)
This research aims at investigating the effect of some organic fertilizers on the growth and yield of green onion plants. The kind of organic fertilizers which can give optimum growth and yield of green onion plants is Bokashi fertilizer. The design used in this experiment is Randomized Block Design (RBD). The treatment used is P0 = without fertilizer or 0 kg swath?1, P1= chicken manure 15 tons ha?1 or 2.4 kg swath?1, P2= cow manure 15 tons ha?1 or 2.4 kg swath?1, P3= vermicompost fertilizer 15 tons ha?1 or 2.4 kg swath -1, P4= bokashi fertilizer 15 tons ha?1 or 2.4 kg swath?1. The observed variables are the height of the plants, the number of leaves, the leaf width, the number of seedlings, fresh residue tan?1, the weight of fresh clump leaves tan?1, the weight of fresh clump leaves ha?1, the number of clump stem?1, and the weight of clump stem?1. Bokashi fertilizer application gives a very real effect to the variable of plants height growth with a total of 37.91%, the number of leaves amounted to 34.81%, the leaves width amounted to 51.35%, the number of seedlings amounted to 48.47%, the fresh residue tan?1 amounted to 44.81%, the weight of fresh clump leaves tan?1 amounted to 19.27%, the weight of fresh clump leaves ha?1 amounted to 50.84%, the number of clump stem?1 amounted to 39.60.%, and the weight of clump stem?1 amounted to 51.98%. Kind of organic fertilizers which can provide the optimum growth and yield of green onion plants is Bokashi fertilizer 15 tons ha?1.